The Effect of Rosa Foetida Extract along with Self-Care Education on Primary Dysmenorrhea: A Prospective Randomized Clinical Trial - Fatemeh Shabani; Shabnam Omidvar; Parvin Sajadi Kaboudi; Hajar Pasha; Soraya Khafri; Hossein Najafzadehvarzi; Fatemeh Nasiri-Amiri; Mahbobeh Faramarzi; Zinatossadat Bouzari (IMR Press, 2024)
Background: Dysmenorrhea is among the most common conditions among young women. Herbal medicine is one of the alternative ways to treat dysmenorrhea. The purpose of this study was to determine the effect of Rosa Foetida extract along with self-care behaviors on primary dysmenorrhea. Methods: A randomized clinical trial was conducted on 135 students residing in dormitories. The subjects were aged 18 to 24 years and unmarried. They divided into three groups of 45. The students received self-care behavior training on dysmenorrhea. After the training, two of the three groups received medications; one with Rosa Foetida extract and another with placebo capsules. The physical appearance of the capsules was similar. The third group received no medication. Data were collected through questionnaires including demographic characteristics questionnaire, a visual analogue scale (VAS), menstrual distress scale questionnaire (MDQ), dysmenorrhea self-care behaviors scale questionnaire (DSCS), and Pictorial Blood Loss Assessment Chart (PBAC). Repeated measurement of analysis of variance (ANOVA) was performed using SPSS software version 22 (IBM Corp., Armonk, NY, USA) to determine and compare the effects of interventions on menstrual pain and distress severity. Results: Comparison of the mean pain intensity before and after intervention implied a reduction in pain; especially in the Rosa Foetida extract group (p < 0.001). Menstrual distress also showed reduction which was greater in the case of the Rosa Foetida group. In addition to those, the reduction of menstrual bleeding was statistically significant in the Rosa Foetida group (p = 0.041). Conclusions: The results showed Rosa Foetida extract prescription, along with self-care behavior education did not have a positive effect on primary dysmenorrhea; however, it was seen to be effective on reducing menstrual distress. Clinical Trial Registration: the study was registered at https://www.irct.ir (registration number IRCT20190318043086N1).